2022
DOI: 10.35314/isi.v7i1.2359
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Dan Implementasi Aplikasi Penjualan Kosmetik Di BMC Berbasis Website Menggunakan Framework Laravel

Abstract: Abstrack -The development of information technology is growing rapidly. Technology also involves various aspects such as aspects of life, the manufacturing industry and the service industry. MSMEs engaged in sales must have clear reporting. Financial reporting can be done through writing in the book, but as the number of orders per day increases, writing in the book is often missed, resulting in an imbalance between sales and purchases. In this study, researchers utilize the website as a developing technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…The issues regarding agile development method in sales information systems have been widely researched, including by [9] which is proposed to design a point-of-sale system at the Eka Putra Store using the agile development method with the aim of helping the store to check sales reports in real time, making transactions easier, and creating a good communication flow between buyers and sellers; 2) Research conducted by [10] developing a point-of-sale system at Cora Petshop using Scrum method as par of agile development to simplify data management and transaction processes where the result gets an average score of 87 using the system usability scale. This shows that the system is quite good and suitable for use; 3) further research by [11] concluded that the design and implementation of a web-based Cosmetic Sales Application in the Bless Me Cosmetic Case Study was very helpful in carrying out the transaction process more accurately and easily, and the use of the agile development method could speed up the development process. Refer to those that the agile development method can quickly and precisely develop a reliable sales information system according to user needs and requirements.…”
Section: Introductionmentioning
confidence: 93%
“…The issues regarding agile development method in sales information systems have been widely researched, including by [9] which is proposed to design a point-of-sale system at the Eka Putra Store using the agile development method with the aim of helping the store to check sales reports in real time, making transactions easier, and creating a good communication flow between buyers and sellers; 2) Research conducted by [10] developing a point-of-sale system at Cora Petshop using Scrum method as par of agile development to simplify data management and transaction processes where the result gets an average score of 87 using the system usability scale. This shows that the system is quite good and suitable for use; 3) further research by [11] concluded that the design and implementation of a web-based Cosmetic Sales Application in the Bless Me Cosmetic Case Study was very helpful in carrying out the transaction process more accurately and easily, and the use of the agile development method could speed up the development process. Refer to those that the agile development method can quickly and precisely develop a reliable sales information system according to user needs and requirements.…”
Section: Introductionmentioning
confidence: 93%
“…Saat ini, masih banyak kendala yang dihadapi dalam melakukan pengelolaan penjualan secara online [5] [6]. Seperti kesulitan dalam melakukan manajemen data barang, pembayaran online yang tidak aman, serta kurangnya laporan penjualan secara real-time [7].…”
Section: Pendahuluanunclassified